1999
DOI: 10.1002/(sici)1099-1220(199909/10)5:5<353::aid-ijpg156>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Infant mortality in the Indian slums: case studies of Calcutta Metropolis and Raipur City

Abstract: Based on data collected through interview of 2142 mothers who had experienced live births and/or infant deaths within one year preceding the date of survey in selected slums of Calcutta Metropolis and Raipur City, this study attempts to elucidate and explain the levels, differentials, causes and determinants of infant mortality in the Indian slums. The infant mortality rate (IMR) in the slums was found to be quite high but lower than that in rural India, underlining the importance of ‘urban residence’ as a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the literature, it can be observed that results vary between country groups and variables and difference depends on data types and methods of estimation (16)(17)(18)(19). As a result of the findings from this study, maternal mortality and infant mortality reduces with 7, and 2000-2014 data from 25 countries (21) it was determined that infant mortality reduced with increased public healthcare spending per capita.…”
Section: Discussionmentioning
confidence: 57%
“…In the literature, it can be observed that results vary between country groups and variables and difference depends on data types and methods of estimation (16)(17)(18)(19). As a result of the findings from this study, maternal mortality and infant mortality reduces with 7, and 2000-2014 data from 25 countries (21) it was determined that infant mortality reduced with increased public healthcare spending per capita.…”
Section: Discussionmentioning
confidence: 57%
“…It should be noted, however, that despite an overall health advantage, enormous differences exists between urban poor women and better off women in accessing to MCH services (Montgomery 2009). The urban population of India (especially those living in urban slums) also suffer notably from poverty, deprivation, and excess infant and child mortality (Gupta and Baghel 1999;Vaid et al 2007). Therefore, policy actions directed towards the improvement of the health of the rural population should not be performed at the expense of other disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…2009a). It has been noted in the slums of India that diarrhoea increases the number of deaths during the rainy season and that under‐five mortality increases during this period (Gupta & Baghel 1999).…”
Section: Discussionmentioning
confidence: 99%